Evaluation of when road space prioritisation/infrastructural improvements for paratransit vehicles is warranted: A case study of Mitchells Plain, Cape Town - Oni, Oluyemi (Department of Civil Engineering, 2019)
In many developing countries, the cities have confined or absolute non-availability of modern quality public transport systems, therefore residents of these cities solely rely on non-scheduled, informal, flexible route transportation system referred to as ‘Paratransit’ to move from one point to another. South Africa being a partly developed and partly developing country also have this particular problem in terms of its public transport system. Some 65% of public transport users make use of paratransit services as a day to day means of transport in South Africa. Paratransit is the most commonly used public transport mode in South African cities as it is relatively affordable and highly flexible. However, it is referred to be very unreliable in terms of journey time and passenger’s waiting time at stops mostly, due to time wasted in traffic congestion and at signalised intersections. So, actions are needed to be taken to improve the travel speed, safety and reliability of paratransit vehicles. In 2007, South Africa’s department of transport envisioned some strategies to revitalise public transport system in South Africa whereby one of the strategies is to replace paratransit called Mini-bus taxi in South Africa with scheduled trunk-feeder services. However, this has proven unachievable, due to resistant from the paratransit association. This dissertation aims to investigate under which traffic condition is road prioritisation/infrastructural improvement is warranted for paratransit vehicles in a trunk-feeder hybrid setting. The dissertation also explored how operations of the paratransit feeders service can be improved through infrastructural improvements and prioritisation on road space using the Mitchells Plain public transport interchange as a case study. An agent-based simulation modelling tool is employed to simulate the present trunk-feeder operations at the Mitchells Plain interchange thereby investigating how the passenger travel performance has been impacted by the configuration and operational characteristics of the current trunk-feeder public transport system. The modelling tool mimic an intermodal trunk feeder operation which include: Passengers arrival at the rank and stops to wait for taxi; boarding and alighting of passengers along the feeder’s route; transfers of passengers alighting from the taxi and walking of the passengers through the interchange to connect to their respective available trunk service public transport system. The main aim of this dissertation is to develop and investigate various infrastructure developments to the road network using road space prioritisation that can be implemented and their effect on the overall efficiency of the paratransit feeder’s system. Each of the proposed infrastructural improvements through prioritisation of paratransit vehicles on road space was tested in a normal and congested traffic condition to evaluate their effectiveness on the operational efficiency of paratransit feeder’s service at varying level of traffic congestion. The effect of the various network infrastructure improvements is being tested using the agent-based simulation tool with the main objectives of improving the operational performance of the paratransit feeder’s services which will lead to a more coordinated, integrated and sustainable trunk-feeder public transport system. The result of the model analysis showed that provision of dedicated lanes for paratransit vehicles is the most efficient infrastructural improvement strategy through road space prioritisation, especially in a traffic-congested route.